2010
DOI: 10.1186/1472-6750-10-24
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic analysis of images of zebrafish treated with Alzheimer's γ-secretase inhibitors

Abstract: BackgroundSeveral γ-secretase inhibitors (GSI) are in clinical trials for the treatment of Alzheimer's disease (AD). This enzyme mediates the proteolytic cleavage of amyloid precursor protein (APP) to generate amyloid β protein, Aβ, the pathogenic protein in AD. The γ-secretase also cleaves Notch to generate Notch Intracellular domain (NICD), the signaling molecule that is implicated in tumorigenesis.ResultsWe have developed a method to examine live zebrafish that were each treated with γ-secretase inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…7B). Consistent with previous findings, we also observed severe developmental defects in DAPT-treated zebrafish embryos, as evidenced by a curved trunk due to the concomitant blockade of Notch signaling by pan-inhibition of γ-secretase (43). In stark contrast to the DAPT-treated zebrafish embryos, CL-387,785-treated embryos exhibited normal somite development with wild-type trunks and tails (Fig.…”
Section: An Shrna Screen Identified Candidate Genes That Differentiallysupporting
confidence: 78%
“…7B). Consistent with previous findings, we also observed severe developmental defects in DAPT-treated zebrafish embryos, as evidenced by a curved trunk due to the concomitant blockade of Notch signaling by pan-inhibition of γ-secretase (43). In stark contrast to the DAPT-treated zebrafish embryos, CL-387,785-treated embryos exhibited normal somite development with wild-type trunks and tails (Fig.…”
Section: An Shrna Screen Identified Candidate Genes That Differentiallysupporting
confidence: 78%
“…1). Several studies applying the zebrafish model in a similar manner have recently been reported in the literature (Ishizaki et al, 2010;Behra et al, 2004;Davidson et al, 2008;Molina et al, 2009;Arslanova et al, 2010;Buckley et al, 2010;Hao et al, 2010;Kokel et al, 2010;Rihel et al, 2010). In the sections below, we summarize some of these examples to illustrate the utility of the zebrafish embryo as a promising system for detecting off-target effects of drug candidates.…”
Section: Primermentioning
confidence: 99%
“…Images are then labeled by experts and classified thanks to the Matlab Gait-CAD toolbox in only two classes. [3] describes a way to automatically obtain images of zebrafish embryos thanks to a motorized microscope, and classifies them manually into phenotypes. [19] developed an automatic system of data acquisition and embryos' analysis in multi-well plates, where manual intervention is still needed to produce analysis routines based on several image segmentations.…”
Section: Related Workmentioning
confidence: 99%